Ethical Empowerment: Integrating Malay Local Wisdom with VCT to Fortify Students' Moral Character in History Learning - Bunari Bunari; Asyrul Fikri; Nurhijrah Binti Zakaria; Ramadhani Lausi Mkumbachi (AL-ISHLAH: Jurnal Pendidikan, 2024)
As juvenile delinquency rates rise in Indonesia, addressing the underlying moral degradation among adolescents becomes crucial. This study investigates the integration of Tanjak Melayu's local wisdom with Value Clarification Technique (VCT) in history education as a strategy for moral character enhancement in students. Using a qualitative ethnographic approach, data was collected through observation, interviews, document reviews, and validity tests, with data analysis performed via triangulation. The study identifies key values of Tanjak Melayu—dignity, politeness, and attractiveness—that can be effectively incorporated into history lessons using VCT. This integration shows a positive impact on student's moral character, providing not only knowledge but also facilitating practical learning tasks. The incorporation of Tanjak Melayu values into educational settings via VCT not only preserves cultural heritage but also actively promotes moral virtues among students. The findings suggest that VCT can be a dynamic tool in moral education, enhancing student engagement and ethical development. This study underscores the potential of culturally integrated education technologies in addressing adolescent behavioral issues. By embedding local cultural values into the curriculum, educational institutions can play a pivotal role in shaping the moral landscape of the next generation. This approach offers a scalable model for similar interventions across diverse educational contexts, aiming to curb juvenile delinquency through enhanced character education. The successful integration of Tanjak Melayu values into history education via VCT demonstrates a viable path towards improving the moral character of students, suggesting that similar cultural and technological adaptations in educational curricula could be beneficial on a broader scale.